Engineering the mode of morphogenetic signal presentation to promote branching from salivary gland spheroids in 3D hydrogels. (15th March 2020) - Samuel, Ronel Z.; Lei, Pedro; Nam, Kihoon; Baker, Olga J.; Andreadis, Stelios T.
ABSTRACT: Previously we developed a fibrin hydrogel (FH) decorated with laminin-111 peptides (L1p -FH) and supports three-dimensional (3D) gland microstructures containing polarized acinar cells. Here we expand on these results and show that co-culture of rat parotid Par-C10 cells with mesenchymal stem cells produces migrating branches of gland cells into the L1p -FH and we identify FGF-7 as the principal morphogenetic signal responsible for branching. On the other hand, another FGF family member and gland morphogen, FGF-10 increased proliferation but did not promote migration and therefore, limited the number and length of branched structures grown into the gel. By controlling the mode of growth factor presentation and delivery, we can control the length and cellularity of branches as well as formation of new nodes/clusters within the hydrogel. Such spatial delivery of two or more morphogens may facilitate engineering of anatomically complex tissues/mini organs such as salivary glands that can be used to address developmental questions or as platforms for drug discovery. Statement of Significance: Hyposalivation leads to the development of a host of oral diseases. Current treatments only provide temporary relief. Tissue engineering may provide promising permanent solutions. Yet current models are limited to salivary spheroids with no branching networks. Branching structures are vital to an effective functioning gland as they increase the surface area/glandular volume ratio of the tissue, allowing a higher output from the small-sized gland. We describe a strategy that controls branch network formation in salivary glands that is a key in advancing the field of salivary gland tissue engineering. Graphical abstract: Image, graphical abstract